Anthropology matters - Fedorak, Shirley (University of Toronto press, 2017)
"Anthropology Matters places the study of anthropology concretely in the world that surrounds it. It takes a question-based approach to introducing important anthropological concepts by embedding those concepts in contemporary global issues that will interest students. The third edition of this popular text has been updated throughout and includes two new chapters: globalization and transnational mobility, and the responsibility of the global community to refugees. The book has also been revised and updated throughout to reflect current events and popular topics, including the impact of social media on social, political, and religious systems, interviews with women who veil, and discussion of design anthropology."--